3 CARDIAC MRI: DETECTION OF MYOCARDIAL INFARCTION IN SYMPTOMATIC PATIENTS WITHOUT CORONARY ARTERY DISEASE UNDERGOING ELECTROPHYSIOLOGICAL TESTING. (1st January 2005) - Kaushal, R.; Fieno, D.; Radin, M.; Narula, J.; Kadish, A.; Goldberger, J.; Shivkumar, K.; Bello, D.
Abstract : Background: Cardiac Magnetic Resonance Imaging (CMRI) can identify myocardial infarction (MI). Detection of unrecognized MI has significant clinical implications. MI is the most common substrate for reentrant ventricular arrhythmias. In patients with coronary artery disease (CAD), infarct size determined by CMRI is a better identifier of patients who have ventricular tachycardia than ejection fraction (EF). In the absence of CAD, MI is rare. We sought to use cardiac MRI in patients without CAD, but with symptoms and/or documented arrhythmias who were undergoing electrophysiological testing. Methods: Planimetry of contrast images obtained from CMRI was used to measure infarct mass and surface area by two readers blinded to electrophysiological study (EPS) results. Results: 23 patients without CAD (mean age: 45±16 years, 48% male, mean EF 49±13%) underwent EPS for evaluation of palpitations (34% of patients), syncope (25%), and/or documented ventricular arrhythmias (34%). 5 patients had hypertrophic obstructive cardiomyopathy (HOCM) and 8 had dilated cardiomyopathy (DCM). During EPS, 15 patients (65%) had no inducible ventricular arrhythmias, 2 patients (8%) had inducible monomorphic ventricular tachycardia (VT), and 6 patients (26%) had inducible polymorphic VT or ventricular fibrillation (PVT/VF). CMRI identified MI in 11 patients (48%) with a mean infarct size as percentage of left ventricular mass of 11±10. MI was visualized in 4/5 patients with HOCM (mostly septal infarcts), 5/8 patients with DCM, and in 2 patients with normal EF. Conclusions: In patients without CAD undergoing electrophysiological testing for symptoms and/or documented ventricular arrhythmias, the prevalence of myocardial infarction is higher than in the general population. Cardiac MRI should be considered in patients presenting with unexplained spontaneous or inducible ventricular arrhythmias.